Certifying the Topology of Quantum Networks: Theory and Experiment - Weinbrenner, Lisa T.; Prasannan, Nidhin; Hansenne, Kiara; Denker, Sophia; Sperling, Jan; Brecht, Benjamin; Silberhorn, Christine; Gühne, Otfried (Physical Review Letters)

Relative-belief inference in quantum information theory - Teo, Y. S.; Shringarpure, S. U.; Jeong, H.; Prasannan, Nidhin; Brecht, Benjamin; Silberhorn, Christine; Evans, M.; Mogilevtsev, D.; Sánchez-Soto, L. L. (Physical Review A)
We introduce the framework of Bayesian relative belief that directly evaluates whether or not the experimental data at hand support a given hypothesis regarding a quantum system by directly comparing the prior and posterior probabilities for the hypothesis. In model-dimension certification tasks, we show that the relative-belief procedure typically chooses Hilbert spaces that are never smaller in dimension than those selected from optimizing a broad class of information criteria, including Akaike's criterion. As a concrete and focused exposition of this powerful evidence-based technique, we apply the relative-belief procedure to an important application: . In particular, just by comparing prior and posterior probabilities based on data, we demonstrate its capability of tracking multiphoton emissions using (realistically lossy) single-photon detectors in order to assess the actual quality of photon sources without making assumptions, thereby reliably safeguarding source integrity for general quantum-information and communication tasks with Bayesian reasoning. Finally, we discuss how relative belief can be exploited to carry out parametric model certification and estimate the total dimension of the quantum state for the combined (measured) physical and interacting external systems described by the Tavis-Cummings model. Published by the American Physical Society 2024

Evidence-Based Certification of Quantum Dimensions - Teo, Y. S.; Shringarpure, S. U.; Jeong, H.; Prasannan, Nidhin; Brecht, Benjamin; Silberhorn, Christine; Evans, M.; Mogilevtsev, D.; Sánchez-Soto, L. L. (Physical Review Letters)
Identifying a reasonably small Hilbert space that completely describes an unknown quantum state is crucial for efficient quantum information processing. We introduce a general dimension-certification protocol for both discrete and continuous variables that is fully evidence based, relying solely on the experimental data collected and no other unjustified assumptions whatsoever. Using the Bayesian concept of relative belief, we take the effective dimension of the state as the smallest one such that the posterior probability is larger than the prior, as dictated by the data. The posterior probabilities associated with the relative-belief ratios measure the strength of the evidence provide by these ratios so that we can assess whether there is weak or strong evidence in favor or against a particular dimension. Using experimental data from spectral-temporal and polarimetry measurements, we demonstrate how to correctly assign Bayesian plausible error bars for the obtained effective dimensions. This makes relative belief a conservative and easy-to-use model-selection method for any experiment. Published by the American Physical Society 2024

Scalable Generation of Multiphoton Entangled States by Active Feed-Forward and Multiplexing - Meyer-Scott, Evan; Prasannan, Nidhin; Dhand, Ish; Eigner, Christof; Quiring, Viktor; Barkhofen, Sonja; Brecht, Benjamin; Plenio, Martin B.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Scalable Generation of Multiphoton Entangled States by Active Feed-Forward and Multiplexing - Meyer-Scott, Evan; Prasannan, Nidhin; Dhand, Ish; Eigner, Christof; Quiring, Viktor; Barkhofen, Sonja; Brecht, Benjamin; Plenio, Martin B.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Direct Measurement of Higher-Order Nonlinear Polarization Squeezing - Prasannan, Nidhin; Sperling, Jan; Brecht, Benjamin; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Experimental entanglement characterization of two-rebit states - Prasannan, Nidhin; De, Syamsundar; Barkhofen, Sonja; Brecht, Benjamin; Silberhorn, Christine; Sperling, Jan (Physical Review A)

Engineering integrated photon pair sources and multiplexed detectors (Conference Presentation) - Meyer-Scott, Evan; Prasannan, Nidhin; Montaut, Nicola; Tiedau, Johannes; Eigner, Christof; Harder, Georg; Sansoni, Linda; Nitsche, Thomas; Herrmann, Harald; Ricken, Raimund; Quiring, Viktor; Bartley, Tim; et al. (Advances in Photonics of Quantum Computing, Memory, and Communication XII)

Engineering integrated sources of entangled photon pairs - Meyer-Scott, Evan; Prasannan, Nidhin; Montaut, Nicola; Tiedau, Johannes; Harder, Georg; Sansoni, Linda; Herrmann, Harald; Eigner, Christof; Ricken, Raimund; Quiring, Viktor; Bartley, Tim; Barkhofen, Sonja; et al. (Frontiers in Optics / Laser Science)

High-performance source of spectrally pure, polarization entangled photon pairs based on hybrid integrated-bulk optics - Meyer-Scott, Evan; Prasannan, Nidhin; Eigner, Christof; Quiring, Viktor; Donohue, John M.; Barkhofen, Sonja; Silberhorn, Christine (Optics Express)